PERAN PERSEPSI DUKUNGAN ORGANISASIONAL DAN KEADILAN DISTRIBUTIF PADA KINERJA KELOMPOK - Danang Sunyoto; R. Nur Budi Setiawan (Jurnal Penelitian Multidisiplin Ilmu, 2022)
Objective - In recent years, more and more studies on organizational involvement have been carried out to find out more, and more broadly, both antecedent and consequent variables, especially those involving individuals as research objects, and only a few studies involving groups as research objects. Therefore, this study aims to examine the antecedent and consequence model of group performance based on Social Exchange Theory. Design/Methodology/Approach - The population of this study is 113 social science study programs at private universities in Yogyakarta and there are 105 study programs that meet the requirements as data. While the object of group research consists of the chairperson and secretary of the department. The research model uses the census model. The independent variables include perceptions of organizational support and distributive justice, as well as the dependent variable, namely group performance. Findings - The results show that perceptions of organizational support and distributive justice do not play a role in the performance of social science study programs at private universities in Yogyakarta. Originality - There are still opportunities to study group performance, both as mediator and predictor using group data objects. Therefore, this study not only offers the use of group data but also provides a wider range of antecedent variables and their consequences based on social exchange theory.